THE DEVELOPMENT MODEL OF CHILDREN WITH SPECIAL NEEDS AT SPECIAL SCHOOL OF BULUROKENG, BIRINGKANAYA DISTRICT OF MAKASSAR CITY (Entrepreneurship Undergraduate Program at Amkop Business School, 2023)
Children with special needs have different characteristics compared to other children in general due to physical, mental, and social activity limitations. Nevertheless, they have the right to receive education tailored to their conditions so that they can lead their lives on an equal footing with other children. Teachers, along with parents, play a crucial role in the growth and development of children in obtaining education. This analysis focuses on the coaching model for children with special needs in the State Special School of Makassar. The analysis focuses on the learning patterns of students in the State Special School of Makassar and the role of teachers in supporting students with special needs in facing the social environment. The research specifically looks into children with special needs who attend the State Special School of Makassar. This is a qualitative research study that uses a phenomenological approach. Informants for the study were purposefully selected. Data collection techniques involved observation, in-depth interviews, and documentation. The research findings indicate that: 1) teachers and parents share responsibility for the education of their children. Effective communication between teachers, parents, and school staff is essential; 2) the role of teachers is vital in educating and guiding their students in adapting to the community environment, starting from the school environment to the broader community.